Nutritional value and therapeutic effect of Mentha pulegium L. and Artemisia abrotanum L. - Selmi, Mejda; Lassoued, Latifa; Chbili, Chahra; Ben Fredj, Maha; Charfeddin , Ridha (Journal of Medicinal Herbs and Ethnomedicine, 2022)
This work is an informative study investigated the nutrient contents and the antioxidant activity of Mentha pulegium L. and Artemisia abrotanum L. two plants largely used in North African traditional medicine as well as in pharmaceutical and agro-alimentary industries. These plants have been used as herbal tea, or powder in herbal remedies, to treat painful menstruation, and gastrointestinal disorders. Recently they were extensively used during the pandemic of Covid-19. Results revealed that both plants were not, only, a good source of essential minerals, like Calcium, Iron, and Magnesium. But they were also rich sources of crude fibre and protein. Vitamin C amount was found 180.94 ±3.01 mg/g100g, with an IC50 value 54.45±25.53 μg/mL 10-1 in M. pulegium and 171.64±3.0 mg/100g with IC50 value 60.61± 19.71 μg/mL 10-1 in A. abrotanum. The antioxidant study showed a high activity that paves the way for the possibility of new health-related uses.